Elaboración y caracterización de morteros de cemento portland reforzados con fibras de polipropileno provenientes de residuos sólidos industriales - Guerra Amaya Juan Camilo; Eljach Forero Julián Andrés (Escuela Colombiana de Ingeniería Julio Garavito, 2021)
This document contains an analysis of the flexural strength and compressive strength of portland cement mortars reinforced with polypropylene fibers obtained from polypropylene straps, polypropylene straps were obtained by taking advantage of waste from logistics operations and packaging. Straps are the most widely used product both for sealing boxes and for tying pallets for national and international transport in Colombia. After obtaining the bands, the fibers were extracted, which were obtained by grouping several bands in a press, where the height of the jaw was adjusted for an adequate depth of cut and subsequently cut by a thin blade. To carry out the study, 3 types of test tube molds were used in which the mortar mixture with polypropylene band fiber was poured. In addition, samples of mortar without fiber were prepared to make the respective comparisons. The samples had 28 days of curing under water and were evaluated with the guide of the NSR-10 standard, obtaining results of compressive strength of 9.06 MPa and flexural strength of 3.04 MPa, for mortars with 0 , 9% PP fiber. Despite the fact that mortar containing 0.9% polypropylene fiber aggregate has lower mechanical properties than mortar without fiber, it classifies within the NSR-10 standard because it requires a minimum resistance of 8.9 MPa compression. Under flexural conditions, the material fractures when reaching a load close to 3 MPa, however, it is observed that the material continues to support load due to the action of the PP fibers that act as a safety device that prevents an abrupt failure.
Keywords: Resistencia a la Compresion-Morteros; Morteros de cemento portland; Fibras de polipropileno; Reciclaje de zunchos; Compression Strength-Mortars; Cement mortars portland; Polypropylene fibers; Recycling of hoops